Sistema tecnológico de aprovechamiento en plantaciones forestales de acacia (Acacia Mangium). San Carlos, Alajuela, Costa Rica. - Villalobos-Barquero, Verónica (Instituto Tecnológico de Costa Rica, 2014)
This project evaluated the technological system used in the exploitation of acacia´s forestry plantations located in San Carlos, Alajuela, Costa Rica. For stages were defined: Tumbling trees, pull trees, hash trees and loading trees. The efficiency of each was determined through a study of time (T) and movement (M) using the sampling methodology proposed by Cordero (1989). Also, the production (m3/hr) of each stage was calculated based on the volume (m3) and the duration of each evaluated day, to obtain the average volume (m3) the Smalian formule was used. The analysis of production costs was conducted by determining the hourly cost (₡/hr) of each of the stages. Based on the hourly cost (₡/hr) and the production obtained (m3/hr), the production´s total cost (₡/m3) calculated. Finally, the days were analyzed, unproductive movements were determined to suppress the necessary and increase the efficiency by redesigning the system currently used, structuring corrective measures to achieve the elimination the main delays. For the work of the tumbling trees, the productive movements of values (27.90%) were obtained and they were higher than the arrears (72.10%); this means that most of the day’s workers were working. The average efficiency of the eight evaluated days was 72.10%. The average production for eight evaluated days was about 9.75 m3. The shafts were dragged by oxen, only one trunk was dragged per cycle and two trunk when the condition was better. The higher productive movements was the pull with a 21.37% of the time´s total and an efficiency of 59.72%. An average production of 5.32 m3 per scheduled time was obtained. For the work of hash "corta" (hashing action) was shown as the productive movement that consumed more time with 28.64%. It was obtained an efficiency of 60.42% resulting an average production of 12.48 m3 per scheduled time. In the loading stage, an average volume (m3) of 4.97 for short logs (1.10 cm) and 7.98 for long logs (1.35 cm) was obtained, plus, a production of 3.52 m3/hr was obtained. According to these results, improvements and appropriate recommendations to the currents system were stablished for each one of the stages. The technological system proposed is described, based on the following goals; reducing occupational hazards for workers, increasing the production and decreasing the production costs of the exploitation system.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2014.
Keywords: Muestreo; Explotación; Estudio de tiempos y movimientos; Producción